2021
DOI: 10.1002/jlcr.3952
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene oxide–polyacrylic acid–folic acid (PEO‐PAAc) nanogel as a 99mTc targeting receptor for cancer diagnostic imaging

Abstract: Nanoparticles are frequently used as targeting delivery systems for therapeutic and diagnostic radiopharmaceuticals. Polyethylene oxide-polyacrylic acid (PEO-PAAc) nanogel was prepared via γ-radiation-induced polymerization. Variable factors affecting nanoparticles size were investigated. The nanogel was radiolabeled with the imaging radioisotope 99m Tc and finally conjugated with folic acid to target folate receptor actively. PEO-PAAc-folic acid gel was characterized by dynamic light scattering (DLS) and atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…In the same year, Soliman et al reported synthesis of polyethylene oxide-polyacrylic acid (PEO-PAA) based nanogels using 𝛾-radiation induced polymerization strategy. [226] The PEO-PAA nanogels were radiolabeled with technetium-99m without any chelator and folic acid was electrostatically bound to the radiolabeled nanogels forming 98 nm [ 99m Tc]Tc-PEO-PAA-folic acid particles. Effect of radiation dose, composition and concentrations of the reactants was investigated.…”
Section: Pet/spect Imagingmentioning
confidence: 99%
“…In the same year, Soliman et al reported synthesis of polyethylene oxide-polyacrylic acid (PEO-PAA) based nanogels using 𝛾-radiation induced polymerization strategy. [226] The PEO-PAA nanogels were radiolabeled with technetium-99m without any chelator and folic acid was electrostatically bound to the radiolabeled nanogels forming 98 nm [ 99m Tc]Tc-PEO-PAA-folic acid particles. Effect of radiation dose, composition and concentrations of the reactants was investigated.…”
Section: Pet/spect Imagingmentioning
confidence: 99%
“…Soliman et al developed a cancer diagnostic imaging device based on polyethylene oxide–PAA nanogel, which is radio-labeled with the imaging radioisotope 99 mTc (metastable nuclear isomer of technetium-99) and then conjugated with folic acid, which act as targeting agent. Biodistribution data indicated a high selective uptake of the prepared complex in cancer muscle respect to the healthy one for both intratumor and intravenous injections, highlighting its potentiality as nanotheranostic device [ 132 ].…”
Section: Polyacrylate: Applicationsmentioning
confidence: 99%
“…Radiation-synthesized nanogels, extensively tested as nanocarriers of drugs, genes and radioisotopes [24][25][26][27][28][29][30][31], can be brought as another excellent example, and various polymers, such as pullulan [32], PVP [33][34][35][36], chitosan and poly(acrylic acid) (PAA) [37], have been exploited with success for this purpose. PAA in particular is a very interesting polymer for biomedical applications, due to its biocompatibility and the contained -COOH groups, enabling the bioconjugation of selected ligands and "smart" drug delivery as a result of changes in the pH of the environment [38].…”
Section: Introductionmentioning
confidence: 99%